أثر تقلبات أسعار النفط على النمو الاقتصادي على المدى البعيد في الجزائر خلال الفترة (1990-2020) دراسة قياسية باستخدام نموذج الانحدار الذاتي للإبطاء الموزع (ardl) - نعمي عبدالله . شيخاوي عبدالعزيز . (جامعة الوادي - University of Eloued, 2022)
ملخص: تهدف هذه الورقة البحثية إلى قياس أثر تقلبات أسعار النفط على النمو الاقتصادي في الجزائر على المدى القريب والبعيد خلال فترة زمنية من سنة 1990 إلى غاية 2020، ولتحقيق أهداف الدراسة، استخدمنا منهجية نموذج الانحدار الذاتي للإبطاء الموزع ARDL بالاعتماد على أسعار النفط كمتغير مستقل ونصيب الفرد الحقيقي من الناتج الإجمالي المحلي متغير تابع كمؤشر للنمو الاقتصادي. حيث تشير نتائج هذه الدراسة إلى وجود علاقة طردية بين أسعار النفط والنمو الاقتصادي في الجزائر خلال فترة الدراسة وبمعنوية إحصائية عالية جداً، حيث أن التغير في سعر النفط بوحدة واحدة سيتغير النمو الاقتصادي ايجابياً بـ 26,32%، مع وجود كذلك علاقة توازنية قصيرة وطويلة الأجل بين أسعار النفط والنمو الاقتصادي خلال فترة الدراسة. Abstract: This research paper aims to measure the impact of oil prices fluctuations on economic growth in Algeria in the short and long term during a period of time from 1990 to 2020, and to achieve the objectives of the study, we used the ARDL methodology based on oil prices as an independent variable and per capita of the gross domestic product as a dependent variable as an indicator of economic growth. The results of this study indicate that there is a direct relationship between oil prices and economic growth in Algeria during the study period and with a very high statistical significance, as the change in the price of oil by one unit will change the economic growth positively by 26,32%, and also the existence of a short- and long-term equilibrium relationship between oil prices and economic growth during the study period.
The impact of oil prices fluctuations on long-term economic growth in Algeria during the period (1990-2020). An econometric study of using Autoregressive Distributed Lag Model (ARDL)
Keywords: أسعار النفط ; نمو اقتصادي ; نموذج ARDL ; علاقة طويلة الأجل